TNF-α Directly Enhances Osteocyte RANKL Expression and Promotes Osteoclast Formation - Marahleh, Aseel; Kitaura, Hideki; Ohori, Fumitoshi; Kishikawa, Akiko; Ogawa, Saika; Shen, Wei-Ren; Qi, Jiawei; Noguchi, Takahiro; Nara, Yasuhiko; Mizoguchi, Itaru (Frontiers in Immunology, 2019)
Osteoimmunology peeks into the interaction of bone and the immune system, which has largely proved to be a multiplex reaction. Osteocytes have been shown to regulate bone resorption through the expression of RANKL in physiologic and pathologic conditions. TNF-α, a product of the immune system, is an important cytokine regulating bone resorption in inflammatory conditions either directly or by increasing RANKL and M-CSF expressions by osteoblasts and stromal cells. The effect of TNF-α on a wide range of cell types has been documented; however, the direct effect of TNF-α on osteocytes has not been established yet. In this study, primary osteocytes were isolated by cell sorting from neonatal calvaria of Dmp1-Topaz mice, which express the green fluorescent protein under the influence of dentin matrix protein 1 promoter. The results show that osteocytes have a significantly higher RANKL mRNA expression when cultured with TNF-α. A co-culture system of osteocytes and TNF receptors I and II deficient osteoclast precursors treated with TNF-α show a significant increase in TRAP-positive cells while cultures without TNF-α failed to show TRAP-positive cells. Additionally, in vivo experiments of TNF-α injected to mouse calvaria show an increase in TRAP-positive cell number in the suture mesenchyme and an increase in the percentage of RANKL-positive osteocytes compared to PBS-injected calvaria. Osteocytes cultured with TNF-α show up-regulation of MAPKs phosphorylation measured by western blot, and adding MAPKs inhibitors to osteocytes cultured with TNF-α significantly decreases RANKL mRNA expression compared to osteocytes cultured with TNF-α alone. We also found that TNF-α activates the NF-κB pathway in osteocytes measured as a function of p65 subunit nuclear translocation. TNF-α directly affects osteocyte RANKL expression and increases osteoclastogenesis; our results demonstrate that osteocytes guard an important role in inflammatory bone resorption mediated by TNF-α.